O‘SMIRLARDA KONSTRUKTIV MULOQOT VA EMOTSIONAL BARQARORLIKNI RIVOJLANTIRIShDA PSIXOKORREKSION USULLARNING O‘RNI - Tojiboyeva, G.R. (SCIENCE and SOCIETY, 2025)
This article analyzes the role of psychocorrectional methods in developing constructive communication and emotional stability among adolescents. A psychocorrectional program including empathy-based interaction, emotional regulation, and stress-management training was developed and experimentally tested. The results demonstrated that psychocorrectional methods effectively reduce interpersonal conflicts and enhance social adaptation and emotional balance among adolescents. The proposed methods can be applied as a practical and scientific basis in the activities of school psychologists.